Microbial fuel cells for wastewater treatment and electricity production: A multi-platform simulation workflow - Muhammad Ali (PLoS ONE, 2026)
The need for sustainable energy generation and efficient wastewater treatment continues to motivate technologies that integrate energy recovery with environmental remediation. Here, a microbial fuel cell (MFC) system is designed and evaluated, leveraging electrogenic microorganisms to produce electricity during wastewater treatment, with a focus on material selection and design configuration. The proposed design integrates key elements including a proton exchange membrane, anodic and cathodic chambers, and an external circuit to support conversion of organic waste to electrical output through an anode–cathode redox cycle. Four software platforms were used to evaluate complementary aspects of the MFC system under stated modeling assumptions. MATLAB was used to model bacterial growth kinetics and anode performance using Butler–Volmer and Monod based relations. DWSIM was used for thermodynamic screening and mass and energy balance calculations to assess feasibility and stream behavior. COMSOL Multiphysics was used to interpret spatial concentration gradients and biofilm related distributions within the anode compartment. MINITAB was used for a design of experiments style statistical screening (ANOVA and Fisher post hoc testing) of five anode materials using a constructed voltage dataset guided by exploratory prototype observations, and electrode material showed a strong effect on voltage output (F = 21779.35, p < 0.001, R² = 99.83%), with platinum producing the highest mean voltage. Post hoc Fisher testing further indicated that the platinum electrode was statistically different from the other materials. Overall, the study establishes a reproducible simulation workflow that supports comparative screening of anode materials and design configurations for MFC based wastewater treatment with energy recovery.